Entrepreneurial attitudes of state program “Paraná improving business" participants, in the county of Francisco Beltrão – PR - Bach, Elisane; Ceretta, Gilberto Francisco; Rocha, Adilson Carlos (Revista de Administração da UFSM, 2018)
This study aims to analyze the existence of differences in the attitudes of entrepreneurs in relation to the economic sectors in which they live their projects of participants of the State Program "Parana Improving Business" in the county of Francisco Beltrão - PR. The study took place between the months of March and August 2013. For the data collection was used a model developed by Lopez Jr. (2005) called Attitude Measurement Instrument Enterprising - IMAE. The questionnaire used is a Likert measurement scale of 10 points with a sample of 101 respondents. The study was carried out by a quantitative approach, in which the data were treated by descriptive statistics. In a comparative analysis of the dimensions, the implementation had higher overall averages of agreement, followed by innovation, power and finally the planning dimension. Comparing the industry sectors, trade and services, it was found that there were subtle differences between them. Thus the research proposed a different analytical perspective to the work of Bosma and Schutjens (2007), exploring the entrepreneurial attitudes with spatial differentiations in Europe, analyzing the attribute of economic sectors as distinction vectors.